2020
DOI: 10.3389/fnhum.2020.600790
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Reactivity and Regulation in Preschool-Age Children Who Do and Do Not Stutter: Evidence From Autonomic Nervous System Measures

Abstract: Purpose: This experimental cross-sectional research study examined the emotional reactivity and emotion regulation in preschool-age children who do (CWS) and do not stutter (CWNS) by assessing their psychophysiological response during rest and while viewing pictures from the International Affective Picture System (Lang et al., 2008).Method: Participants were 18 CWS (16 boys and two girls; mean age 4 years, 5 months) and 18 age- and gender-matched CWNS. Participants' psychophysiological responses were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 124 publications
0
7
0
Order By: Relevance
“…Physiological Parameters in CWS vs. CWNS There is limited research that examines the physiological parameters of CWS vs. CWNS. Recent studies [74,81,100] have shown significant skin conductance (EDA), heart rate (HR), and respiratory effort (RSA) differences in CWS and CWNS in different conditions. A recent study [81] showed that during stress-inducing conditions, the CWS exhibited a higher heart rate (HR) and a lower RSA than the CWNS.…”
Section: Related Work and Background Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiological Parameters in CWS vs. CWNS There is limited research that examines the physiological parameters of CWS vs. CWNS. Recent studies [74,81,100] have shown significant skin conductance (EDA), heart rate (HR), and respiratory effort (RSA) differences in CWS and CWNS in different conditions. A recent study [81] showed that during stress-inducing conditions, the CWS exhibited a higher heart rate (HR) and a lower RSA than the CWNS.…”
Section: Related Work and Background Discussionmentioning
confidence: 99%
“…Recent studies [74,81,100] have shown significant skin conductance (EDA), heart rate (HR), and respiratory effort (RSA) differences in CWS and CWNS in different conditions. A recent study [81] showed that during stress-inducing conditions, the CWS exhibited a higher heart rate (HR) and a lower RSA than the CWNS. A study [89] on AWS has developed a multi-layered perceptron (MLP) neural network-based stuttering disfluency event classification system that takes respiration signals as input.…”
Section: Related Work and Background Discussionmentioning
confidence: 99%
“…Psycho-physiological features relevant to affective states and stuttering individual’s physiological responses are extracted from each 2s segments. We extracted the heart rate (HR) from the raw ECG signal, since a recent study [ 74 ] of heart rate (HR) in relation to stressful situations indicates that children who stutter showed a significantly higher HR than CWNS. Electrodermal activity (EDA) signals increases and shows spontaneous fluctuations during arousal [ 9 , 58 ].…”
Section: Description Of the Dataset And Our Data Collection Proceduresmentioning
confidence: 99%
“…This section evaluates the discriminative capability of the raw physiological features for the CWNS vs. CWS classification task. Notably, recent literature [ 9 , 58 , 66 , 71 , 74 ] have established that the HR, EDA, RSP-rate, RSP-amp are effective features for affective states and stuttering individual’s physiological arousal detection. Hence, this section aims to identify the features’ relative importance rather than feature selection.…”
Section: Experiments and Evaluation Of Mi-milmentioning
confidence: 99%
“…When measured at rest, there are no differences between these two components in children who stutter and their peers who do not. In the case of challenging conditions, however, children who stutter tend to be more emotionally reactive and need to employ more emotion regulation skills (Tumanova, Wilder, Gregoire, Baratta & Razza, 2020). Furthermore, Adigun (2020) pointed out that during the teenage period of stuttering children, levels of EI are impacted by their socioeconomic status, social support, and perceived quality of life.…”
Section: Stuttering In Relation To Communication and Emotional Intell...mentioning
confidence: 99%